Uma leitura crítico – emancipatória da violência na escola: as lutas e os jogos de oposição como forma de (res)significação. - Silva, Sorlei Silva e (Universidade Federal do Tocantins, 2019)
The present work has as objective to problematize the meanings of the violence in the school through the content fights and of opposition games, with students of the sixth year of the elementary school of a full time teaching institution located in the city of Tocantinópolis - TO.